2021
DOI: 10.1038/s41598-021-85738-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of patient specific, realistic, and reusable video assisted thoracoscopic surgery simulator using 3D printing and pediatric computed tomography images

Abstract: Herein, realistic and reusable phantoms for simulation of pediatric lung video-assisted thoracoscopic surgery (VATS) were proposed and evaluated. 3D-printed phantoms for VATS were designed based on chest computed tomography (CT) data of a pediatric patient with esophageal atresia and tracheoesophageal fistula. Models reflecting the patient-specific structure were fabricated based on the CT images. Appropriate reusable design, realistic mechanical properties with various material types, and 3D printers (fused d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Moreover, material stiffness should be in the in vivo range for coronary arteries. In the frame of the InSilc project, the authors had access to the PolyJet technology, which is reported as one of the standards in the literature of 3D-printing of anatomical phantoms because of its high resolution ( 12 ). This would allow mimicking the dimensions, shape, and all morphological aspects (e.g., stenoses) affecting the outcome of the deployment in terms of lumen gain and malappositions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, material stiffness should be in the in vivo range for coronary arteries. In the frame of the InSilc project, the authors had access to the PolyJet technology, which is reported as one of the standards in the literature of 3D-printing of anatomical phantoms because of its high resolution ( 12 ). This would allow mimicking the dimensions, shape, and all morphological aspects (e.g., stenoses) affecting the outcome of the deployment in terms of lumen gain and malappositions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Chen et al made 3D–printed models for surgical planning in the first case of a right-to-left inverted living-donor lobar lung transplantation, followed by multiple successful cases [ 53 ]. The development of a patient-specific, realistic, and reusable VATS simulator using 3D printing technology was also reported for a pediatric patient with an esophageal atresia and tracheoesophageal fistula [ 54 ]. A similar technique is the use of 3D stereoscopic vision using 3D polarized glasses or head-mounted displays.…”
Section: Current Status Of 3d Ct Images In Thoracic Surgerymentioning
confidence: 99%
“…AI-Jabir et al presented an Advanced Scope Trainer (AST, Mediskills Limited, Northampton, UK), which allows the training of both basic and advanced procedures [18]. However, there still remain challenges in developing a realistic artificial organ phantom system with detailed anatomy, providing realistic imaging results as well as enabling quantitative feedback on the surgical performance to the trainees [19,20].…”
Section: Introductionmentioning
confidence: 99%